Anagrus nedotepae sp. n. (Hymenoptera: Mymaridae), an egg parasitoid of Nedotepa curta (Hemiptera: Cicadellidae), a pest of coconut palm in West Africa - Triapitsyn, Serguei V.; Kwadjo, K. Eric; Rosete, Yaima Arocha (Zootaxa, 2017)
A new Afrotropical species of Anagrus Haliday (Hymenoptera: Mymaridae), A. nedotepae Triapitsyn sp. n., is described and illustrated. The type series was reared from parasitized eggs of the leafhopper Nedotepa curta Dmitriev (Hemiptera: Cicadellidae) during a survey for its natural enemies in Côte d’Ivoire. This peculiar leafhopper, recently described from Ghana (Dmitriev 2016), lays its eggs on leaflets of coconut palm, and could be an economically important pest of this crop in West Africa, particularly because it is a suspected vector of the phytoplasma associated with the Côte d’Ivoire Lethal Yellowing disease of coconut, as characterized by Arocha-Rosete et al. (2014). Coconut lethal yellowing diseases cause severe economic losses to the very important coconut growing industry in several West African countries and elsewhere, being considered a threat of global economic and social significance (Gurr et al. 2016). Thus, the parasitoid may be of potential importance for natural biological control of this pest and urgently needs a scientific name to be used in further publications on its biology and ecology. Such studies are currently underway by the second author, who collected the type series of the new species.